Extracts of Artocarpus communis Induce Mitochondria-Associated Apoptosis via Pro-oxidative Activity in Human Glioblastoma Cells - Lee, Chiang-Wen; Hsu, Lee-Fen; Lee, Ming-Hsueh; Lee, I.-Ta; Liu, Ju-Fang; Chiang, Yao-Chang; Tsai, Ming-Horng (Frontiers in Pharmacology, 2018)
Glioblastoma multiforme (GBM) is an extremely aggressive and devastating malignant tumor in the central nervous system. Its incidence is increasing and the prognosis is poor. Artocarpin is a natural prenylated flavonoid with various anti-inflammatory and anti-tumor properties. Studies have shown that artocarpin is associated with cell death of primary glioblastoma cells. However, the in vivo effects and the cellular and molecular mechanisms modulating the anticancer activities of artocarpin remain unknown. In this study, we demonstrated that treating the glioblastoma cell lines U87 and U118 cells with artocarpin induced apoptosis. Artocarpin-induced apoptosis is associated with caspase activation and poly (ADP-ribose) polymerase (PARP) cleavage and is mediated by the mitochondrial pathway. This is associated with mitochondrial depolarization, mitochondrial-derived reactive oxidative species (ROS) production, cytochrome c release, Bad and Bax upregulations, and Bcl-2 downregulation. Artocarpin induced NADPH oxidase/ROS generation plays an important role in the mitochondrial pathway activation. Furthermore, we found artocarpin-induced ROS production in mitochondria is associated with Akt- and ERK1/2 activation. After treatment with artocarpin, ROS causes PI3K/Akt/ERK1/2-induced cell death of these tumor cells. These observations were further verified by the results from the implantation of both U87 and U118 cells into in vivo mouse. In conclusion, our findings suggest that artocarpin induces mitochondria-associated apoptosis of glioma cells, suggesting that artocarpine can be a potential chemotherapeutic agent for future GBM treatment.